O ensino da tabuada no contexto das ações de estudo propostas por Davýdov e colaboradores - EDISÉIA SUETHE FAUST HOBOLD; JOSÉLIA EUZÉBIO DA ROSA (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2017)
TEACHING THE MULTIPLICATION TABLE IN THE CONTEXT OF STUDY ACTIONS PROPOSED BY DAVÝDOV AND CO-WORKERS ABSTRACT This research was developed in the Mathematics education context based on the assumptions of the cultural-historical theory, with emphasis on the work of Davýdov, doctor in psychology and Vygotsky's follower. Davýdov coordinated the process for elaboration of a proposal for mathematics teaching in Russia, and published through textbooks and teacher's guiding books. This material is the data source for the research, which consisted in Davýdov's tasks, and the aim is constituted in the investigation of the conceptual movement, Davýdov's proposition to teach the multiplication table through study actions. The results indicate the author's proposition for teaching the multiplication table contemplates the interrelations of arithmetic, algebraic and geometrical significations on the movement that involves the general, universal, particular and singular on the context of study actions. KEYWORDS mathematics education; cultural-historical theory; Davýdov; teaching proposition; multiplication table. LA ENSEÑANZA DE LA TABLA DE MULTIPLICAR EN EL CONTEXTO DE LAS ACCIONES PROPUESTAS POR DAVÝDOV Y COLABORADORES RESUMEN La investigación fue desarrollada en el contexto de la educación matemática basada en los presupuestos de la teoría histórico-cultural con énfasis para la obra de Davýdov, doctor en psicología y seguidor de Vigotski. Davýdov coordinó el proceso de elaboración de una propuesta para la enseñanza de matemática en Rusia, y publicó por medio de libros didácticos y manuales de orientación para profesores. Ese material es la fuente de datos de la investigación, que consiste en las tareas de Davýdov, y cuyo objetivo es constituido en investigar el movimiento conceptual impreso en la proposición de Davýdov para la enseñanza de la tabla de multiplicar, por medio de acciones de estudio. Los resultados indican que la proposición del autor para la enseñanza de la tabla de multiplicar contempla la interrelación de las significaciones aritméticas, algébricas y geométricas en el movimiento que involucra lo general, universal, particular y singular en el contexto de acciones de estudio.